Peningkatan Pengetahuan dan Keterampilan Organik dan PNS Politeknik Angkatan Darat dalam Penanganan Cedera Olahraga: Improved Knowledge and Skills of Organic and PNS of Politeknik Angkatan Darat in Sports Injury Management - Pribadi, Heri Purnama; Sugiarto, Dinta; Abdullah, Ahmad; Yunus, Mahmud (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Injury is one of the most common health problems experienced by TNI members in carrying out their duties as soldiers. Injuries to the TNI cause performance that is not optimal in carrying out tasks, especially field tasks. This community service activity aims to increase the knowledge and skills of coaches, organics, and civil servants in the Army Polytechnic environment. The activity was carried out on 24 August 2023 at the Politeknik Angkatan Darat, involving 19 organics and civil servants as participants. The activity began with the material delivery, then measuring participants' knowledge and skills in injury management. The activity results increased from 10.26 ± 1.24 to 12.47 ± 2.25. So, with the Community Service activities carried out, Poltekad Organics and civil servants can carry out independent handling of acute and subacute sports injuries to optimize healing and prevent recurrent injuries.